Application of GIS and Remote Sensing for Hydropower Development in Nepal - Pathak, Mahesh (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Nepal is endowed with abundant water resources from the availability point of view. Hydropower is considered as a viable means of economic growth for the country's overall development. The river and physiographic characteristics of Nepal offer immense possibilities for the development of hydropower schemes of different scales, and various national and international agencies have expressed keen interest. On the other hand, Nepal's biodiversity resources, a fragile landscape, scattered settlement patterns and natural resource based rural livelihoods are directly affected by hydropower development. Use of recent information about place, people and scientific analysis is crucial for addressing the environmental and socio-economic impacts of development activities. Geographic Information System (GIS) and Remote Sensing (RS) technology have the capabilities to create, update and manage recent information about the earth's surface and its integration with socio- economic information; but these technologies have not been used properly for the hydropower development sector in Nepal. This paper is about the application of GIS and Remote sensing technology to make the hydropower development environment friendly and to create less impact upon the rural livelihood. Key words: GIS, Remote Sensing, hydropower, watershed management, Nepal doi: 10.3126/hn.v3i0.1920 Hydro Nepal Journal of Water, Energy and Environment Issue No. 3, July 2008. Page: 42-45